A Surgical Kit for Stem Cell-Derived Retinal Pigment Epithelium Transplants: Collection, Transportation, and Subretinal Delivery - Li, Kang V.; Flores-Bellver, Miguel; Aparicio-Domingo, Silvia; Petrash, Carson; Cobb, Hannah; Chen, Conan; Canto-Soler, M. Valeria; Mathias, Marc T. (Frontiers in Cell and Developmental Biology, 2022)
Transplantation of stem cell-derived retinal pigment epithelium (RPE) cells is a promising potential therapy for currently incurable retinal degenerative diseases like advanced dry age-related macular degeneration. In this study, we designed a set of clinically applicable devices for subretinal implantation of RPE grafts, towards the overarching goal of establishing enabling technologies for cell-based therapeutic approaches to regenerate RPE cells. This RPE transplant kit includes a custom-designed trephine for the production of RPE transplants, a carrier for storage and transportation, and a surgical device for subretinal delivery of RPE transplants. Cell viability assay confirmed biocompatibility of the transplant carrier and high preservation of RPE transplants upon storage and transportation. The transplant surgical device combines foldable technology that minimizes incision size, controlled delivery speed, no fluid reflux, curved translucent tip, usability of loading and in vivo reloading, and ergonomic handle. Furthermore, the complementary design of the transplant carrier and the delivery device resulted in proper grasping, loading, and orientation of the hiPSC-RPE transplants into the delivery device. Proof-of-concept transplantation studies in a porcine model demonstrated no damage or structural change in hiPSC-RPE transplants during surgical manipulation and subretinal deployment. Post-operative assessment confirmed that hiPSC-RPE transplants were delivered precisely, with no damage to the host retina or choroid, and no significant structural change to the hiPSC-RPE transplants. Our novel surgical kit provides a comprehensive set of tools encompassing RPE graft manufacturing to surgical implantation rendering key enabling technologies for pre-clinical and clinical phases of stem cell-derived RPE regenerative therapies.